All-Step-in-One Test Kit for Paraquat Detection in Water and Vegetable Samples - Sangsum C. (2023)
This work presents the first development of an all-steps-in-one test kit for the determination of paraquat in natural water, and vegetable and agricultural samples. A handheld photometer incorporated with a magnetic stirrer was used to complete the steps of extraction, mixing, and detection. Paraquat produces a blue free radical ion via a reduction with sodium dithionite in alkaline conditions. Sodium dithionite powder was investigated for the enhancement of reagent stability duration, which was added directly into sample solution that showed insignificant difference in sensitivity as compared with that of the solution format of sodium dithionite. The developed test kit showed good performance with the linear calibration of 0.5 to 10 mg L−1 with a high coefficient of determination (r2 = 0.9947). The lower limit of quantitation (LLOQ = 3SD of intercept per slope) carried out from the method using the handheld photometer was 0.50 mg L−1. The limit of detection (LOD) by naked eye was 0.30 mg L−1. The recovery study was acceptable in the range of 101–115%. Intraday (n = 3) and interday (n = 3) precision was less than 1%. On the basis of the significance test at the 95% confidence interval, quantitative results of the developed test kit agreed well with those from high-performance liquid chromatography (HPLC). To the best of our knowledge, this is the first report demonstrating an online extraction for vegetables incorporated into a test kit, applicable for on-site analysis. Single-point calibration based on the Beer–Lambert law also demonstrated the measurement of paraquat. In testing with a nominal standard solution of 5.00 mg L−1 paraquat, the reading concentration was 5.09 ± 0.03 mg L−1 paraquat (n = 20) with a K value of 0.0967 (close to the slope of multipoint calibration). This research is a direct benefit to agricultural products and the health of a population for the analysis of pesticides and herbicides.